Vulnerabilidade costeira e classificação da orla de praias de Marapanim, Nordeste Paraense - NEGRÃO, Yago de Souza (2018)
The coastal zone is an extreme dynamic region, due to many factors on the coast line. So, she is subject to many modifications because of the erosion processes a coastal growth. Besides, she has a great value for the human occupation because of its attractive landscape, even though in the most of times it happens in a disorder way, without taking care of the regional characteristics. Localized on the northeast region of Pará, the city of Marapanim is considered one of the most important touristic spot, with its beautiful beaches which bring hundreds of tourists every year, specially the beach of Crispim and Santa Maria. However, these stretches are presenting problems related to the coast erosion, that makes a lot of damage to the residents, and to the population. Still, a good number of residents in these places are in an irregular way and without any planning. In this sense, the coastal management shows as an important tool to make the territorial planning better. So, this work has the objective to evaluate the coastal vulnerability of the beaches of Crispim, Marudá and Santa Maria (Marapanim/PA) in face of the erosion processes, and classify their margin considering their urban occupation. For that it was realized a field campaign for the data acquisition for the tables of coastal vulnerability and stretch classification. The methodology used was proposed by Lins-de-Barros (2005) and modified according to the characteristics of the study area. The step 1 consisted on the study of the physical vulnerability to erosion, the step 2 on the study of the urban indicators, the step 3 on the risk degree, the step 4 on the damage degrees and the identified loss, the step 5 on the study of the adaptation and perception types, the step 6 on the definition of the special areas to the planning, and the 7 on the proposals of measures and actions for the planning and coastal management. Besides that, maps and graphics were made on the software’s ArcGis 10, Surfer 10 and OriginLab 9, referring to the analyzed variables. The physical vulnerability had a great variability on the margin Crispim-Santa Maria, being that on the central regions of the beach of Crispim and Marudá, she was classified as very high due to show many damaged or destroyed constructions, and without showing natural structures of protection of the coast line, because of the constant loss of the natural landscape characterization. On Santa Maria the vulnerability was low, due to its localization inside the estuary and a low urbanization. The risk degree had a great variability, also, being that the higher classifications were on the same regions with developed urbanization, as the risk is associated with the presence of the urban occupation on the coast line. About the x typology of the stretch, the coast showed some natural stretch A, stretch in process of urbanization B1 and B3, and urbanized stretch C3 and C4. The stretch Crispim-Santa Marina has some peculiar diversities and, due to this, management plans should be developed to suit each region to promote orderly and safe occupation for the residents.